Nontraumatic Myositis Ossificans of Hip: A Case Presentation - Yunus Oc; Muhammed Sefa Ozcan; Hasan Basri Sezer; Bekir Eray Kilinc; Osman Tugrul Eren (Case Reports in Orthopedics)
In most of the cases trauma is the leading etiology and the nontraumatic myositis ossificans (MO) is a very rare condition. We present an MO case without any trauma occurring. A 36-year-old female patient with a history of pain and restriction of range of motion of the left hip was admitted. Hip motions were restricted with 10–60° of flexion, 10° of internal rotation, 20° of external rotation, 10° of abduction, and 10° of adduction. There was no history of trauma and familial involvement. The biopsy of the lesion revealed mature bone tissue confirming our diagnosis of MO. The mass was removed surgically and postoperatively the patient was treated with a single dose radiotherapy with 800 gyc. MO is a benign and well differentiated bone formation or in other words heterotopic ossification of the muscle tissue. It has a prevalence of less than 1/1 million. Trauma is the most frequent etiological factor seen in almost 60–75% of the cases. Nontraumatic MO is very rare in the literature. Our patient had no history of trauma or familial involvement. Combination of the surgical excision with radiotherapy in the treatment of the MO of the hip may give satisfactory results.